(untitled) (Communications in Computational Physics, 2018)
This paper develops an enhanced finite element method for approximating a class of variational problems which exhibits the Lavrentiev gap phenomenon in the sense that the minimum values of the energy functional have a nontrivial gap when the functional is minimized on the spaces W^1,1 and W^1,∞. To remedy the standard finite element method, which fails to converge for such variational problems, a simple and effective cut-off procedure is utilized to design the (enhanced finite element) discrete energy functional. In essence the proposed discrete energy functional curbs the gap phenomenon by capping the derivatives of its input on a scale of O(h^−α) (where h denotes the mesh size) for some positive constant α. A sufficient condition is proposed for determining the problem-dependent parameter α. Extensive 1-D and 2-D numerical experiment results are provided to show the convergence behavior and the performance of the proposed enhanced finite element method.